Simultaneous Tomography and Diffraction Analysis of Creep Damage - Pyzalla, A; Camin, B; Buslaps, T; Di Michiel, M; Kaminski, H; Kottar, A; Pernack, A; Reimers, W (Science (American Association for the Advancement of Science), 2005)
Creep damage by void nucleation and growth limits the lifetime of components subjected to loading at high temperatures. We report a combined tomography and diffraction experiment using high-energy synchrotron radiation that permitted us to follow in situ void growth and microstructure development in bulk samples. The results reveal that void growth versus time follows an exponential growth law. The formation of large void volumes coincides with texture evolution and dislocation density, reaching a steady state. Creep damage during a large proportion of sample creep life is homogeneous before damage localization occurs, which leads to rapid failure. The in situ determination of void evolution in bulk samples should allow for the assessment of creep damage in metallic materials and subsequently for lifetime predictions about samples and components that are subject to high-temperature loading.